2000
DOI: 10.54991/jop.2000.159
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the deccan intertrappean flora of Nawargaon, Wardha District, Maharashtra, India

Abstract: Eight fossil wood species are described from the Deccan Intertrappean beds of Nawargaon, Wardha District, Maharashtra. India. The fossil flora, so far, recovered from the Nawargaon area indicates that tropical evergreen forests with some moist deciduous plants were nourishing around Nawargaon area in Central India during Early Tertiary in contrast to mixed deciduous type of present day forest. The habit and habitat of the modem comparable taxa suggest prevalence of tropical humid climate in the area during Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Prakash and Dayal (1964) instituted the genus Elaeocarpoxylon to accommodate the woods of Elaeocarpus L. and Slonea L. So far, five species of the genus, viz. E. antiquum Prakash and Dayal (1964), E. mandlaensis Lakhanpal et al (1978) E. mohgaoense Trivedi and Srivastava (1980), E. ghughuensis Awasthi et al (1996) and E. nawargaonensis Khare et al (2000) are described from the Deccan Intertrappean beds of Madhya Pradesh and Maharashtra. One of its species, E. hailakandiensis is reported from the Neogene deposits of Tipam Sandstone, Assam (Prakash & Tripathi, 1975).…”
Section: Genus -Elaeocarpoxylon Prakash and Dayal Emend Prakash And T...mentioning
confidence: 99%
“…Prakash and Dayal (1964) instituted the genus Elaeocarpoxylon to accommodate the woods of Elaeocarpus L. and Slonea L. So far, five species of the genus, viz. E. antiquum Prakash and Dayal (1964), E. mandlaensis Lakhanpal et al (1978) E. mohgaoense Trivedi and Srivastava (1980), E. ghughuensis Awasthi et al (1996) and E. nawargaonensis Khare et al (2000) are described from the Deccan Intertrappean beds of Madhya Pradesh and Maharashtra. One of its species, E. hailakandiensis is reported from the Neogene deposits of Tipam Sandstone, Assam (Prakash & Tripathi, 1975).…”
Section: Genus -Elaeocarpoxylon Prakash and Dayal Emend Prakash And T...mentioning
confidence: 99%
“…Amongst them, in having well developed paratracheal vasicentic, aliform to aliform-confluent parenchyma Barringtonioxylon arcotense Awasthi (1970) and Barringtonioxylon mandlaensis Bande and Khatri (1980) can be differentiated with the present fossil wood in which scanty paratracheal to uniseriate vasicentric parenchyma is present in addition to diffuse to diffuse-in-aggregate apotrachaeal parenchyma. While identification of B. mandlaensis reported by Khare et al (2000) from the Wardha District is doubted by Kar et al (2004) Description-Fungal spores/conidia are profusely found endogenously in the vessels of the fossil wood 6;. Very fine mycelium is also seen at places but it is broken, ill preserved and difficult to reveal structural details.…”
Section: Family-lecythidaceaementioning
confidence: 99%
“…Amongst them, three species are reported from the Deccan Intertrappean beds of India. These are: Barringtonioxylon deccanense Shallom (1960) and B. eopterocarpoxylon Prakash and Dayal (1965) from Intertrappean sediments of Mahurzari, Nagpur, Maharashtra; B. mandlaensis Bande and Khatri (1980) from Intertrappean sediments of Parapani, Mandla (now Dindori), Madhya Pradesh and Wardha District, Maharashtra (Khare et al, 2000). Three species are reported from Neogene sediments of India, viz., B. arcotense Awasthi (1970) (Awasthi & Mehrotra, 1993) and Tipam Sandstone, Assam (Prakash et al, 1994) and also from Infratrappean sediments of Lameta Formation, Maharashtra.…”
Section: Family-lecythidaceaementioning
confidence: 99%